BETA-AMYLOID AS PATHOGENESIS OF ALZHEIMER DISEASE - Mahendri Pattni, Kadek Ary (E-Jurnal Medika Udayana; vol 2 no 8 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Alzheimer disease is often causing cognitive decline in elder population. The incidence of this disease is increasing by the age, about 0,3% to 0,6% it affects individuals aged 65 to 69 years, and 5,3% - 7,5% affects individuals aged 65 to 69 years. Alzheimer also affects individuals aged less then 65 years and known as early onset of Alzheimer disease that is caused by increasing of Beta-Amyloid aggregation from the mutation of amyloid precursor protein (APP). From the accumulation of this substance may trigger the cascade lost of some synaps in the brain and arising Alzheimer type of Dementia. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Alzheimer, Beta-Amyloid